2016
DOI: 10.3390/children3040032
|View full text |Cite
|
Sign up to set email alerts
|

The Parent Psychological Flexibility Questionnaire (PPFQ): Item Reduction and Validation in a Clinical Sample of Swedish Parents of Children with Chronic Pain

Abstract: In pediatric chronic pain, research indicates a positive relation between parental psychological flexibility (i.e., the parent’s willingness to experience distress related to the child’s pain in the service of valued behavior) and level of functioning in the child. This points to the utility of targeting parental psychological flexibility in pediatric chronic pain. The Parent Psychological Flexibility Questionnaire (PPFQ) is currently the only instrument developed for this purpose, and two previous studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…Parent Psychological Flexibility. Parent psychological flexibility regarding their child’s pain was assessed using the Parent Psychological Flexibility Questionnaire, 10-item version (PPFQ-10) [ 16 , 17 ]. Items are rated on a 7-point Likert scale, from 0 for “Never” to 6 for “Always”.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parent Psychological Flexibility. Parent psychological flexibility regarding their child’s pain was assessed using the Parent Psychological Flexibility Questionnaire, 10-item version (PPFQ-10) [ 16 , 17 ]. Items are rated on a 7-point Likert scale, from 0 for “Never” to 6 for “Always”.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the total score, the measure includes three subscales: value based action (3 items), emotional acceptance (4 items), and pain willingness (3 items). Items were reverse scored where indicated [ 16 , 17 ] and summed to calculate the total score and three subscales, with higher scores indicating greater psychological flexibility. Internal consistency for the total score within this sample was good (α = 0.83) and ranged from acceptable to good for subscales (value based action α = 0.75, emotional acceptance α = 0.88, pain willingness α = 0.72).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Items are rated on a scale from 0 (never true) to 6 (always true), and examples of items are: “Even though my child has pain we can continue to do things that are important and enjoyable” and “My child’s pain makes it impossible to focus on anything else” (reversed scoring). In this study, we used a 10-item version of the instrument, with seven reversed items and a maximum score of 60, on the basis of a psychometric evaluation and factor analysis of a Swedish version of the instrument [34]. At pre-treatment assessment, Cronbach’s alpha for PPFQ in this sample was 0.82.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological flexibility has a positive impact on mental health (9). In fact, psychological flexibility is the core treatment target in ACT (10). Various studies have focused on the effects of ACT on mental disorders; the results of a meta-analysis have shown that ACT impacts anxiety (11); the results of another study show that ACT is a promising treatment for depression (12).…”
mentioning
confidence: 99%